Kajian Semiotika dalam Novel Bidadari Berbisik Karya Asma Nadia - Srikandi Monalisa; Sri Rahayu (UIR Press, 2022)
Semiotics is a science that systematically studies signs which are grouped into three types, namely icons, indexes and symbols. This study aims to identify and analyze the icons, indices and symbols, markers and the relationship of the signifiers contained in the novel Bidadari Berklik by Asma Nadia. The research problems are (1) how is the semiotics of the iconic aspects in the novel Bidadari Berbisaan by Asma Nadia? (2) how is the semiotics of the index aspect in the novel Bidadari Whispering by Asma Nadi? (3) how is the semiotics of the symbol aspect in the novel Bidadari Berklik by Asma Nadia?. The approach in this study uses a qualitative approach. The type of language and literature research is the type of library study. The research method used is content analysis method. The technique of collecting research data uses hermeneutic techniques, namely reading techniques. The theory used in this research is the theory of semiotics, icons, indexes, and symbols proposed by Emzir and Rohman (2015), Danesi (2010), Pradopo (2012), Santoso (2013). The data collection technique in this research uses hermeniutic technique. Data analysis techniques with content analysis, classifying, analyzing and concluding data. The results of this research are 26 icons, 66 indexes, and 39 data symbols. For example, icons, indexes and symbols in Asma Nadia's novel Bidadari Whispering